1982
DOI: 10.1007/bf02618575
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a reptilian epithelioid skin cell line derived from the green sea turtle,Chelonia mydas

Abstract: A continuous line of epithelioid cells was established from explant skin tissues of the green sea turtle, Chelonia mydas. These cells, designated GTS, have been subcultured more than 60 times in commercially available mammalian cell culture medium supplemented with 5% bovine calf serum. Of those temperatures tested, optimal growth was achieved at 30 degrees C although replication occurred between 16 and 37 degrees C. These cells may be held as monolayers at 8 degrees C or stored frozen in growth medium contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 13 publications
6
16
0
Order By: Relevance
“…All 13 cell lines showed no growth when incubated at either 15 ° C or 37 ° C. This result is consistent with that of Moore and coworkers (24) but conflicts with findings by Koment and Haines who demon-strated rapid replication of turtle skin cells at 37 ° C and minor growth at 16 ° C (16). Despite their sensitivity to low temperature, these newly established green turtle cell lines remained viable over 3 mo.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…All 13 cell lines showed no growth when incubated at either 15 ° C or 37 ° C. This result is consistent with that of Moore and coworkers (24) but conflicts with findings by Koment and Haines who demon-strated rapid replication of turtle skin cells at 37 ° C and minor growth at 16 ° C (16). Despite their sensitivity to low temperature, these newly established green turtle cell lines remained viable over 3 mo.…”
Section: Discussionsupporting
confidence: 88%
“…It should be noted that this optimal growth temperature was not due to the initial adaptation of green turtle cells cultivated at 30 ° C since the initial growth of green turtle cells progressed much slower when an alternative temperature (25 ° C) was selected (data not shown). This optimum growth temperature was identical to that reported for three cell lines previously established from green turtles (16,20,24). Interestingly, the incubation temperature for maximal growth was slightly higher than the preferred temperature (21-28 ° C) of green turtles in nature (15).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…At low temperature (19°C), cells were unable to replicate (data not shown). Koment and Haines (1982) reported that normal epithelioid skin cells of the green sea turtle, Chelonia mydas, were successfully grown at 30°C, although replication occurred between 16 and 37°C. At 37°C however, the cells were noticeably ragged and granulated, resulting from acceleration of metabolism by rapid change in pH.…”
Section: Discussionmentioning
confidence: 99%
“…These include various cells from the heart of the box turtle, Terrapene carolina (Clark and Karzon, 1967;Huang and Clark, 1967), the skin of the green sea turtle, Chelonia mydas (Koment and Haines, 1982), the heart and lung of the Tokai gecko, Gecko gecko, the heart, liver and kidney of the green iguana, Iguana iguana, the heart of the side-necked turtle, Podocnemis unifilis, and the spleen of the Grecian tortoise, Testudo graeca (Clark et al, 1970). Cell lines have also been established from cutaneous fibropapillomas of C. mydas (Mansell et al, 1989;Lu et al, 1999).…”
Section: Introductionmentioning
confidence: 99%